Intrinsic alignment as an RSD contaminant in the DESI survey. Issue 1 (10th April 2023) - Lamman, Claire; Eisenstein, Daniel; Aguilar, Jessica Nicole; Brooks, David; de la Macorra, Axel; Doel, Peter; Font-Ribera, Andreu; Gontcho A Gontcho, Satya; Honscheid, Klaus; Kehoe, Robert; Kisner, Theodore; Kremin, Anthony; et al.
ABSTRACT: We measure the tidal alignment of the major axes of luminous red galaxies (LRGs) from the Legacy Imaging Survey and use it to infer the artificial redshift-space distortion signature that will arise from an orientation-dependent, surface-brightness selection in the Dark Energy Spectroscopic Instrument (DESI) survey. Using photometric redshifts to downweight the shape–density correlations due to weak lensing, we measure the intrinsic tidal alignment of LRGs. Separately, we estimate the net polarization of LRG orientations from DESI's fibre-magnitude target selection to be of order 10 −2 along the line of sight. Using these measurements and a linear tidal model, we forecast a 0.5 per cent fractional decrease on the quadrupole of the two-point correlation function for projected separations of 40–80 h −1 Mpc. We also use a halo catalogue from the Abacussummit cosmological simulation suite to reproduce this false quadrupole.